Radiology Department: A Potential Source of Multidrug-Resistant Microorganisms: A Cross-Sectional Study at Tertiary Hospital, Palestine - Zena Odeh; Safaa Abatli; Mohammad Qadi (Canadian Journal of Infectious Diseases and Medical Microbiology, 2023)
Introduction. Globally, healthcare facilities face a great challenge in the form of hospital-acquired infections (HAIs). Aside from the morbidity and mortality they cause, these illnesses are also extremely costly. Research on infection transmission in the medical field has been considerable, but not so much in the radiology department. Aim. This study aims to identify the presence of multidrug-resistant (MDR) microbes on surfaces that are frequently touched in computed tomography (CT), magnetic resonance imaging (MRI), ultrasound (US), plain X-ray examination rooms, and portable radiography that are susceptible to contamination as well as to investigate the potential dangers of contracting MDR organisms to patients and healthcare providers. Materials and Method. In this study, 160 swab samples were collected from the radiology department during May and June 2022. Samples were obtained from 80 predefined surfaces twice within and outside of CT and MRI examination rooms as well as from US and plain X-ray machines and portable X-ray machines. Samples were taken at 7:00 a.m. using cotton swabs following the regular cleaning procedure. Bacterial colony-forming units (CFUs) per square centimeter were calculated after swabbing a 100 cm2 surface. Results. Nearly all of the surfaces tested had bacterial CFUs. The highest contamination rate was found on keyboards ranging from (1.2–8) CFU/cm2, the sides of patient tables (1.2–20) CFU/cm2, knee coil (2.4–3) CFU/cm2, and patient leg supports (1.2–8) CFU/cm2. A noticeable increase in the contamination was noticed in June compared to May, and this was consistent with the increase in the number of isolated patients in the hospital, the workload in the radiology department, and the number of patients referred to the hospital. In our study, none of the examined sites showed contamination with MDR Gram-negative bacteria such as extended-spectrum beta-lactamases producing Enterobacterales (ESPL) or Carbapenemase-producing Enterobacterales (CPE). On the other hand, methicillin-resistant Staphylococcus (MRS), vancomycin-resistant Staphylococcus (VRS), and vancomycin-resistant Enterococcus (VRE) were detected. Conclusion. All of the radiology department equipment and sites could be a source of bacterial infection including MDR, so the obligatory and committed disinfection protocol must be revised and implemented in the morning and between patients.